Chemical treatment of sugarcane bagasse and its influence on glyphosate adsorption - Da Penha Bezerra, Williene Faria [UNESP]; Dognani, Guilherme [UNESP]; De Alencar, Laura Neves [UNESP]; Parizi, Marcela Prado Silva [UNESP]; Boina, Rosane Freire [UNESP]; Cabrera, Flávio Camargo; Job, Aldo Eloízo [UNESP] (FapUNIFESP (SciELO), 2022)
Due to the production rates of sugarcane, nowadays, the sugarcane bagasse stemming in the sugar and alcohol industry is the agro-industrial waste produced in greater volume throughout in Brazil. In 2019, about 192 million tons of this waste were generated. The use of this waste has been the aim of researches around the world, with emphasis on applications that aim to meet the prerogatives of the concept of circular economy. Within this scenario, sugarcane bagasse (SB) was treated in an alkaline medium, forming an adsorbent material, SBNaOH. The effects of chemical treatment were evaluated for surface properties and for glyphosate removal in an aqueous medium. The adsorptive phenomenon was studied through isotherm tests. The results obtained were fitted to classical models of Langmuir, Freundlich and Dubinin-Radushkevich. The characterization indicated that the chemical treatment promoted an important change in the surface of the residue, increasing the surface area. SB and SBNAOH had a feasible behavior as adsorbent and good performance in the removal of the herbicide, presenting values greater than 65% of under all working conditions. The theoretical adsorption saturation governed by Dubinin-Radushkevich (qS) was in the order of 8.988 mg/g (R2=0.988) for SB at 120 minutes of contact and maximum adsorption capacity by Langmuir (Qmax) was 13.720 mg/g (R2=0.984) for SBNaOH at 40 minutes of contact. The process was governed by the exchange or sharing of electrons. The adsorbate is distributed heterogeneously on the SB surface, justifying the presence of active sites with greater ionic strength, and homogeneously on the SBNaOH surface (monolayer). In general, the treated sugarcane bagasse, coming from an agro-industrial residue, proved to be an alternative and promising biosorbent for the removal of glyphosate from aqueous systems, thus generating a new application of this residue.
Tratamento químico de bagaço de cana-de-açúcar e sua influência na adsorção de glifosato
Keywords: Adsorption; Agro-industrial waste; Alkaline treatment; Biosorbent; Herbicide